WORKING REGIMES FOR FRICTION STIR PROCESSING OF ALUMINIUM ALLOY A6061 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Friction Stir Processing (FSP) is a method for solid-state processing, in which a rotating tool is moved onto the material surface to modify the microstructure and thus obtain improved properties of the material surface. We study the effects of FSP on aluminium alloy A6061-T651 using a tool made at the Institute of Metal Science, Equipment, and Technologies with Centre for Hydro- and Aerodynamics (IMSETCHA) of the Bulgarian Academy of Sciences. The tool has a threaded pin with three flutes and a concave shoulder. Optimal process parameters should always be chosen for the treatment of new materials and when a new instrument is used in order to achieve target properties of processed zone. The appropriate properties, like strength, hardness, corrosion resistance, etc. require process parameters that are correctly configured. The most influential parameters on friction stir processing are direction of rotation of the tool, rotation speed, and traverse speed of the processing. In this paper, we investigate the properties of the processed zone for a total of 16 regimes: 4 rotation speeds (900, 1100, 1300, 1500 rpm) and 4 traverse speeds (15, 30, 45, 60 mm/min) using counterclockwise rotation, comparing the results with a previous study using clockwise rotation. Metallographic inquiry, hardness and tribological tests are used to estimate the stirred zone quality.